Log in to add a comment

## Answers

The Brainliest Answer!

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Two objects with initial masses of m1 and m2 and initial velocity of u1 and u2 with final velocities after collision to be v1 and v2 after time t.

F1 = M2(V2-U2)/T

F2 = M1(V1-U1)/T

F1 = −F2

M2(V2-U2)/T=-( M1(V1-U1)/T)

M2V2 - M2U2 /T = - (M1V1 - M1U1 )/T

M2V2 - M2U2 = -M1V1 + M1U1

M2V2+M1V1 = M2U2 - M1U1

Therefore total momentum before and after collision is equal.

F1 = M2(V2-U2)/T

F2 = M1(V1-U1)/T

F1 = −F2

M2(V2-U2)/T=-( M1(V1-U1)/T)

M2V2 - M2U2 /T = - (M1V1 - M1U1 )/T

M2V2 - M2U2 = -M1V1 + M1U1

M2V2+M1V1 = M2U2 - M1U1

Therefore total momentum before and after collision is equal.

The change in momentum in A = m1v1 - m1u1

The force by A on B [F1] = m1v1 - m1u1 / t (change in momentum / time)........(i)

The change in momentum in B = m2v2 - m2u2

The force by B on A [F2] = m2v2 - m2u2 / t.............(ii)

**BY NEWTON'S 3RD LAW F1 = - F2 ( F action = - F reaction)**

m1v1 - m1u1 / t = - ( m2v2 - m2u2 / t)

m1v1 - m1u1 = - m2v2 + m2u2

or

m2u2 + m1u1 = m1v1 + m2v2 (INITIAL MOMENTUM = FINAL MOMENTUM)

So, momentum before collision = momentum after collision